Penguin chicks benefit from elevated yolk androgen levels under sibling competition. - Maud Poisbleau (Public Library of Science (PLoS), 2012)
Crested penguins (genus Eudyptes) have a peculiar hatching pattern, with the first-laid egg (A-egg) hatching after the second-laid egg (B-egg) and chicks from A-eggs typically having a much lower survival probability. Maternal yolk androgens have been suggested to contribute to the competitive superiority of the B-chick in southern rockhopper penguins Eudyptes chrysocome, given their important role in mediating sibling competition in other species. We therefore increased the yolk androgen levels in freshly-laid eggs and examined the consequences for sibling competition--via effects on embryonic developmental times, chick growth and early survival. We placed one androgen-treated egg and one control egg into each foster nest, matching them for mass, laying date and laying order. The androgen treatment did not significantly affect embryonic developmental times or chick measurements at hatching. However, elevated yolk androgen levels benefitted chick growth in interaction with the number of siblings in a brood. Chicks from androgen-treated eggs had faster growth in the presence of a sibling than chicks from control eggs. Under these circumstances they also had a higher survival probability. Thus maternal androgens appear to reinforce the observed hatching pattern, facilitating brood reduction. This contrasts to most previous studies in other species where yolk androgens have been shown to compensate for the negative consequences of delayed hatching within the brood hierarchy.